THE DEPENDENCE OF QUALITY OF UKRAINIAN POLITICAL ELITE OF WITH THE DEGREE OF DEVELOLMENT OF CIVIL SOCIETY - Довбня, О. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The interrelation of the level of development of civil society and the quality of the political elite is researched. The link between the political elite with organizations of the civil society, which represent the constructive opposition to the authorities, is underlined. The difficulties of evolving of political elite of Ukraine due to preservation of some principles, characteristic of the Soviet-era nomenclature are analyzed. The role of the local self-management in the process of improvement of the political elite and its activities is shown.